OPERATIONAL COST REDUCTION OF GAS-THERMAL POWER PLANT BASED ON BAT ALGORITHM - Agus Sofwan; M. Febriansyah; Sugeng Sugeng (Universitas Mercu Buana, 2021)
An optimised operation of a thermal power plant is required to optimise fuel consumption cost. It is still high and becomes a problem of economic dispatch in the operation of the plant. Load scheduling and generator capacity are needed to get optimal plant operation, especially energy usage. This paper presented a thermal power plant operation analysis to obtain optimum operational energy costs using the Bat Algorithm (BA). The actual data of 6 thermal power plants to serve the peak loads in 2018 is used for the calculation. The problem solution is simulated and calculated using maximum (95%) capacity and the BA method. The Simulation is done by using MATLAB software. The generator unit and generator load characteristics are collected to obtain objective functions and constraint functions. BA completes this function to get the lowest energy. The BA method will be compared with the calculation of real-time energy generation without BA to analyse its accuracy. The total operational cost of the actual power plant without BA is 1,988,410. BA simulation gave the total energy cost is 1,653,374. So, the generated energy savings is 16.85%, or 335,036 MW reduction.